Die NAIRU – eine post-keynesianische Interpretation - Eckhard Hein (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2004)
In this paper the New Keynesian long run equilibrium view of a non-accelerating-inflation-rate-of-unemployment (NAIRU) determined by structural characteristics of the labour market, wage bargaining institutions and social benefit systems is challenged by a Post-Keynesian view. In a Post-Keynesian model the NAIRU can only be interpreted as a short run barrier to employment arising from inflation fuelled by distribution conflict, which is enforced by monetary policies. In the long run, the development of the NAIRU follows actual unemployment and hence effective demand. Different adjustment channels are identified. It is also shown that effective coordination of wage bargaining is a better means to stabilise inflation rates and employment than monetary policies. – – In this paper the New Keynesian long run equilibrium view of a non-accelerating-inflation-rate-of-unemployment (NAIRU) determined by structural characteristics of the labour market, wage bargaining institutions and social benefit systems is challenged by a Post-Keynesian view. In a Post-Keynesian model the NAIRU can only be interpreted as a short run barrier to employment arising from inflation fuelled by distribution conflict, which is enforced by monetary policies. In the long run, the development of the NAIRU follows actual unemployment and hence effective demand. Different adjustment channels are identified. It is also shown that effective coordination of wage bargaining is a better means to stabilise inflation rates and employment than monetary policies.
Keywords: 330